The Evolutionary Stability of Moral Foundations - Avataneo, Michelle; Norman, Thomas; Persico, Nicola (Quarterly Journal of Economics, 2025)
ABSTRACT Moral foundations theory is an influential empirical description of moral perception. According to this theory, individuals make moral judgments based on five distinct “moral foundations”: care, fairness, loyalty, authority, and sanctity. We provide a theory that explores the claimed evolutionary basis for these moral foundations. The theory conceptualizes these five moral foundations as specific modifications of fitness payoffs in a 2 × 2 game. We find that the five foundations are distinguishable from each other and evolutionarily stable. However, they are not a minimal set: strict subsets of the foundations suffice to describe all preferences that are evolutionarily stable. Not all evolutionarily stable foundations deliver social fitness improvement over the Nash equilibrium in the fitness game: we characterize which do. Finally, we study moral overdrive, that is, the situation in which the moral component of preferences totally dominates fitness payoffs and drives decision making entirely. While every one of the five foundations is compatible with moral overdrive in at least one fitness game, there is no fitness game in which moral overdrive is compatible with social fitness improvement. These results are partially extended to n × n games. We derive two testable implications from the theory and find empirical support for them.